Exploring organisational mechanisms in PRO-based follow-up in routine outpatient care - an interpretive description of the clinician perspective - Caroline Trillingsgaard Mejdahl; Liv Marit Valen Schougaard; Niels Henrik Hjollund; Erik Riiskjær; Kirsten Lomborg (BMC, 2018)
Abstract Background Patient-reported outcome (PRO)-based follow-up is a new model of service delivery, where PRO measures are used as the very basis for demand-driven outpatient follow-up in patients with chronic diseases. Adopting the clinicians' perspective, we aimed to explore what happens when PRO-based follow-up is implemented in routine clinical practice. We also aimed to identify organisational mechanisms related to PRO-based follow-up. Methods The methodological approach of this interview study is interpretive description, informed by a perspective of critical realism. Semi-structured interviews were conducted with 13 clinicians (eight nurses and five physicians) working with PRO-based follow-up in outpatient care for epilepsy in the Central Denmark Region. Results PRO-based follow-up gave rise to ambivalence in clinicians. Seen from the clinicians' perspective, PRO-based follow-up could both increase and decrease the quality of follow-up. Moreover, PRO-based follow-up both enhanced and impaired clinicians' work experiences. Additionally, the clinicians used strategies to ease some of the perceived disadvantages. The clinicians did extra tasks and worked around the scope of PRO-based follow-up. Thus, clinicians constituted a professional buffer as they deflected some of the negative mechanisms associated with PRO-based follow-up. Conclusions As a model of a service delivery, PRO-based follow-up is highly dependent on the clinicians' day-to-day management of the system, and mechanisms related to routine use of PRO measures in outpatient follow-up are complex. Paying attention to the organisational settings is critical for PRO-based follow-up to improve quality of care and enhance patient-centred care.